(untitled) (American Journal of Islam and Society, 2016)
Over the last decade, public discourse in Europe and North America has been overwhelmingly in favor of banning the face veil (niqab). Politicians like Jack Straw in the UK or John Charest in Québec have commented on its putative hindrance to community integration due to its covering of the face. So a book entitled Face Politics would seem to offer some insights into this anti-niqab dynamic. A quick perusal of the index for “niqab,” “Islam,” and “Muslim women,” however, comes up unexpectedly empty. What, then, is “face politics” and how can an academic discussion about the “face” not mention niqab, arguably one of the most burning issues of “face politics” this century? The book is a profound, intellectually challenging, sometimes dense, and yet empathetic and beautifully written exploration of how contemporary western politics is predicated around individuality and the separatedness of being, signified by the idea of the face as a “window onto the [individual’s] soul” (p. 165). Because she believes that “a politics that makes the face is a politics that produces the person as an object” (p.7), the author wishes to propose a different concept of the face, that of a mask hiding our inseparable connectedness, and concludes that such an alternative would lead to a profoundly different, and better, political society, one symbolized by the concept of the tango. Indeed, the tagline on the dedication page is “If the face is a politics, dismantling the face is also a politics,” from French philosopher Gilles Deleuze and psychoanalyst Félix Guattari’s 1980 book A Thousand Plateaus: Capitalism and Schizophrenia ...